Observation of a new interference phenomena in internal conical diffraction - DONEGAN, JOHN; LUNNEY, JAMES (My University, 2015)
Conical diffraction is observed in biaxial materials when a beam of light is directed along one of the two optic axis directions. When the beam is directed close to but not along an optic axis, a rich interference pattern is observed beyond the material. We observe some of the previously predicted low intensity interference patterns, representing a qualitatively new optical phenomenon in biaxial materials.
PUBLISHED
Keywords: Conical diffraction; Conical diffraction; Nanoscience & Materials